A Potassium Diboryllithate: Synthesis, Bonding Properties, and the Deprotonation of Benzene. Issue 38 (17th August 2016) - Ohsato, Takuto; Okuno, Yuri; Ishida, Shintaro; Iwamoto, Takeaki; Lee, Ka‐Ho; Lin, Zhenyang; Yamashita, Makoto; Nozaki, Kyoko
Abstract: A potassium diboryllithate (B2 LiK) was synthesized and structurally characterized. DFT calculations, including NPA and AIM analyses of B2 LiK, revealed ionic interactions between the two bridging boryl anions and Li + and K + . Upon standing in benzene, B2 LiK deprotonated the solvent to form a hydroborane and a phenylborane. On the basis of DFT calculations, a detailed reaction mechanism, involving deprotonation and hydride/phenyl exchange processes, is proposed. An NBO analysis of the transition state for the deprotonation of benzene suggests that the deprotonation should be induced by the coordination of benzene to the K + . Abstract : A 'LiK ' of work : A potassium diboryllithate, B2 LiK, was synthesized and structurally characterized. The bonding situation in this compound was examined by NMR, XRD, NPA, and AIM analyses. B2 LiK is able to deprotonate benzene with concomitant formation of phenylborane as the major product. A detailed reaction mechanism based on DFT calculations suggests that the deprotonation of benzene should be initiated by a transition state involving the coordination of benzene to K + .